Identification of Bacteria which Infected The Garra Rufa Fish Cyprinion Macrostomus at Quarantine Office of Soekarno-Hatta Airport - Mustahal Mustahal; Anik Waqiah (Jurnal Perikanan dan Kelautan, 2012)
A study has  been carried out to identify the bacteria that  infected the  garra  rufa  fish (Cyprinion macrostamus) which have been transported through the Quarantine Office of Soekarno - Hatta Airport.  These fishes were among the freshwater commodities which frequently transported throughout various countries, because they were commonly used for decreasing the effect of psoriasis in a feet  spa  treatment, by  feeding  the  dead  cells of  feet  skin.  Therefore, the possibility of spreading the diseases during  the treatment must be anticipated. In this study the bacteria samples were taken from the fish skin and then cultured in the laboratory. After purification of the  cultures,  the bacteria were then tested by a serial  microbiological methods to identify the bacteria. The results showed that the Garra rufa  fish (Cyprinion macrostomus)  observed in this study  indicated  the presence of   bacteria  of  (+) Motile Aeromonas Septicaemia,  and  (-) of   Motile Aeromonas Septicaemia, which were among the diseases of quarantine fishes.  While the Aeromonas hydrophylla  was also found out, even though not  included as diseases of quarantine fishes. Therefore, they may received the health  certificate  for  fish and fish product for export as well as  for therapeutic purposes .Keyword: garra rufa, bacterial identification, bacterial pathogen